Empowering Communities through Digital Skills Training in Simeulue Village - Rahmat Jete; Rina Farah (Pengabdian: Jurnal Abdimas, 2024)
Background. Social entrepreneurship has emerged as a strategic approach to address socio-economic disparities, especially in remote communities where access to economic opportunities and institutional support is limited. Purpose. This study aims to explore the development of social entrepreneurship in the remote region of Sidenreng Rappang, Indonesia, focusing on community-driven initiatives and their socio-economic impacts. Method. Employing a qualitative case study methodology, data were collected through in-depth interviews, participant observation, and document analysis involving local entrepreneurs, community leaders, and development agencies. Results. The findings reveal that successful social entrepreneurship in the region is driven by strong local leadership, the utilization of indigenous knowledge, and adaptive strategies that align with the community’s cultural and ecological context. Challenges identified include limited access to capital, insufficient training in entrepreneurial skills, and weak institutional support. Conclusion. The study concludes that fostering social entrepreneurship in remote areas requires a hybrid support system involving education, mentorship, policy facilitation, and community empowerment. This research contributes to the growing body of literature on inclusive development by highlighting the contextual dynamics of entrepreneurial ecosystems in marginalized areas